Learning from Linnaeus: towards developing the foundation for a general structure concept for morphology - Vogt, Lars (Zootaxa, 2008)
Morphology has fundamental problems regarding aperspectival objectivity of its data—morphological terminology is often based on homology assumptions, lacks standardization, and has problems with comparability, reproducibility, and transparency. This is astonishing given that with his sexual system Linnaeus had already established a high degree of aperspectival objectivity in morphology that unfortunately has been lost subsequently. In the first part of the article a brief introduction to the history of classification is given that provides an answer to the question why morphology only initially has been gripped by the general trend towards objectification that started in the seventeenth century. The conceptual shortcomings of Aristotle’s concept of essences and its link to the definition of species and taxa in natural philosophy play an important part in this development. The only solution to the problem of essences was to link it to the evolutionary concept of homology, which explains why morphological terminology today often rests on homology assumptions. By taking a closer look at Linnaeus’ sexual system, basic principles for developing a general structure concept for morphology are discussed, which would provide the conceptual basis for establishing a high degree of aperspectival objectivity for morphological data. The article concludes with discussing the role of data bases and ontologies for developing a data standard in morphology. A brief introduction to the basic principles of Resource Description Framework (RDF) ontologies is given. A morphological ontology has high potential for establishing a general morphological structure concept if it is developed on grounds of the following principles: morphological terms and concepts must be defined taxon-independently, homology-free, preferably purely anatomically, and if functionally only by clearly indicating the trait’s active participation in a specific biological process.